Peran Komunitas Red Batik Dalam Mendukung Kota Solo Sebagai Kota Kreatif - Muhammad Nur Indra Wicaksono; I Made Adikampana (JURNAL DESTINASI PARIWISATA, 2019)
Solo City has so many communities with different aspects of value from one another. The Red Batik community is chosen based on its credibility and is one of the most productive communities in Solo City. This study aims to determine the establishment of the Red Batik Community, as well as identify and explain the role of the Red Batik Community in supporting the City of Solo as a Creative City. The research methodology used in this study is research with in-depth interview techniques, observation, literature study and documentation. In addition to using the concept of community-based tourism, role concepts and creative city concepts to review existing problems. The Red Batik community becomes a space for informal education by providing a forum for people who want to get involved or engage in industry and creative activities, especially costumes and carnivals, preserve traditional markets that are characteristic of Solo City, and hold interesting shows for tourists. As a city full of cultural values, Solo City is an attractive place for tourists to visit. Keywords: Creative City, Roles, Community Based Tourism, Red Batik Solo.